Factors Influencing Organizational Citizenship Behavior of Employees - Kadek Dwi Ambarawati; I Gede Aryana Mahayasa (Management and Applied Social Studies Review, 2023)
Purpose – The purpose of this study was to determine the effect of organizational commitment and job satisfaction on organizational citizenship behavior (OCB). Methodology – The total population used is 35 people who are all employees of PT. SUSILA in Denpasar. This research is a population research or census study. Data collection using a questionnaire technique. Furthermore, the data were analyzed using multiple linear regression analysis techniques. Findings – The results of the study indicate that there is a partial and simultaneous positive and significant influence between organizational commitment and job satisfaction on organizational citizenship behavior. Originality – The results showed that private employees also found that organizational commitment and job satisfaction would be able to encourage employees to do extra work outside of their main job.